Time course of efficacy of ubrogepant for the acute treatment of migraine: Clinical implications - Goadsby, Peter J; Blumenfeld, Andrew M; Lipton, Richard B; Dodick, David W; Kalidas, Kavita; M Adams, Aubrey; Jakate, Abhijeet; Liu, Chengcheng; Szegedi, Armin; Trugman, Joel M (Cephalalgia, 2021)
Background The full utility of an acute treatment requires examination of the entire time course of effect during a migraine attack. Here the time course of effect of ubrogepant is evaluated. Methods ACHIEVE-I and -II were double-blind, single-attack, Phase 3 trials. Adults with migraine were randomised 1:1:1 to placebo or ubrogepant (50mg or 100mg, ACHIEVE-I; 25 mg or 50 mg, ACHIEVE-II). Pain freedom, absence of most bothersome symptom, and pain relief were assessed at various timepoints. Samples were collected for pharmacokinetic analysis. Data were pooled for this post-hoc analysis. Results Participants’ (n = 912 placebo, n = 887 ubrogepant 50 mg, pooled analysis population) mean age was 41 years, with a majority female and white. Pain relief separated from placebo by 1 h (43% versus 37% [OR, 95% CI: 1.30, 1.0–1.59]), absence of most bothersome symptom by 1.5 h (28% versus 22% [1.42, 1.14–1.77]), and pain freedom by 2 h (20% vs. 13% [1.72, 1.33–2.22]). Efficacy was sustained from 2–24 h (pain relief: 1.71, 1.1–2.6; pain freedom: 1.71, 1.3–2.3) and remained separated at 48 h (pain relief: 1.7, 1.1–2.6; pain freedom: 1.31, 1.0–1.7). Pharmacokinetic analysis demonstrated maximum plasma concentrations were achieved at 1 h, with pharmacologically active concentrations reached within 11 min and remaining above the EC90 for nearly 12 h. Conclusions Evaluation of the time course of effect of ubrogepant showed pain relief as the most sensitive and earliest measure of clinical effect, followed by absence of most bothersome symptom, and pain freedom. Efficacy was demonstrated out to 48 h, providing evidence of the long-lasting effect of ubrogepant. This evaluation supports the role of examining the entire time course of effect to understand fully the utility of an acute treatment for migraine. Trial registration: ACHIEVE I (ClinicalTrials.gov, NCT02828020) and ACHIEVE II (ClinicalTrials.gov, NCT02867709)